Application of transparent insulation materials to buildings heating in passive solar systems - Koczyk, Halina; Górka, Andrzej; Basińska, Malgorzata (Journal of Civil Engineering and Management, 2002)
The aim of this paper is to present a numerical model, based on the finite difference method and able to describe the heat transfer in a room with indirect passive solar system in form of transparent insulation material (TIM) wall. Results of numerical calculations of thermal fields in TIM wall, in room with passive solar system, under climatic conditions of typical meteorological year for Poznan, are presented. Also the estimation of energy savings for selected rooms with TIM wall is given. Construction of a numerical model of building includes calculation of distribution of temperatures in all walls forming the enclosure, composition of system of energy balance equations for nodes representative of rooms and its solution. In numerical calculations of the thermal states of rooms with transparent walls, an analysis of respective components of thermal balance there has been conducted, in conjunction with required radiator heating power of automated heating installation – coacting with passive solar systems (PSS), as well as variability of η in the comparative year including months from September to April. Frist Published Online: 30 Jul 2012